A chemical sensor based on a photonic-crystal L3 nanocavity defined in a silicon-nitride membrane - Deasy, Kieran; Sediq, Khalid N.; Brittle, Stuart; Wang, Tao; Davis, Frank; Richardson, Tim H.; Lidzey, David G. (Royal Society of Chemistry, 2014)
The application of a silicon-nitride based L3 optical nanocavity as a chemical sensor is explored. It is shown that by adjusting the thickness of an ultra-thin Lumogen Red film deposited onto the nanocavity surface, the fundamental optical mode undergoes a progressive red-shift as the layer-thickness increases, with the cavity being able to detect the presence of a single molecular monolayer. The optical properties of a nanocavity whose surface is coated with a thin layer of a porphyrin-based polymer are also explored. On exposure of the cavity to an acidic-vapour, it is shown that changes in the optical properties of the porphyrin-film (thickness and refractive index) can be detected through a reversible shift in the cavity mode wavelength. Such effects are described using a finite difference time-domain model.